The STEREO Mission - Russell, C.T.; Russell, C.T. (Springer New York : Imprint: Springer, 2008)
The STEREO mission uses twin heliospheric orbiters to track solar disturbances from their initiation to 1 AU. This book documents the mission, its objectives, the spacecraft that execute it and the instruments that provide the measurements, both remote sensing and in situ. This mission promises to unlock many of the mysteries of how the Sun produces what has become to be known as space weather.